Financial development and health care expenditure in Sub Saharan Africa Countries - Jaison Chireshe; Matthew Kofi Ocran (Cogent Economics & Finance, 2020)
The study aimed to examine the relationship between financial development and health care expenditure in 46 Sub Saharan Africa (SSA) countries. The paper argues that health care expenditure is a key transmission mechanism through which financial development influences better health outcomes. The study used random and fixed effects as well as instrumental variable estimation methods using data from 1995 to 2014. The results showed that financial development leads to increased health care expenditure. In terms of policy implications, the findings underscore the need to foster financial development in SSA economies to assist with domestic resource mobilisation to finance health care expenditure.
Keywords: E22; E44; G00; I00; 330; financial development; health care expenditure; random and fixed effects; SubSaharan Africa